2007
DOI: 10.1016/j.jmb.2007.06.047
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Structure of Retinylidene Ligand of Rhodopsin Probed by Molecular Simulations

Abstract: SummaryRhodopsin is currently the only available atomic-resolution template for understanding biological functions of the G protein-coupled receptor (GPCR) family. The structural basis for the phenomenal dark state stability of 11-cis-retinal bound to rhodopsin and its ultrafast photoreaction are active topics of research. In particular, the β-ionone ring of the retinylidene inverse agonist is crucial for the activation mechanism. We analyzed a total of 23 independent, 100-ns all-atom molecular dynamics simula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
54
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 79 publications
6
54
0
Order By: Relevance
“…Our previous work showed that after the 11-cis to all-trans isomerization retinal became more flexible (46,47,67). Here we extend that view to understand how all-trans retinal behaves in the active Meta-II state versus the preactive Meta-I state ( Fig.…”
Section: Retinalsupporting
confidence: 74%
“…Our previous work showed that after the 11-cis to all-trans isomerization retinal became more flexible (46,47,67). Here we extend that view to understand how all-trans retinal behaves in the active Meta-II state versus the preactive Meta-I state ( Fig.…”
Section: Retinalsupporting
confidence: 74%
“…The absence of line broadening or resonance splitting indicated that we had trapped a spectroscopically well defined Meta II state. Molecular dynamics (MD) simulations and 2 H NMR measurements on rhodopsin have suggested that there are two major conformations of the ␤-ionone ring, one with a positively twisted C6 -C7 single bond and one with a negatively twisted C6 -C7 single bond (33,34). As described below, 13 C chemical shift and DARR NMR measurements suggest that, predominantly, a single conformation exists in rhodopsin and in Meta II.…”
Section: Methodsmentioning
confidence: 94%
“…This follows our protocol previously applied to rhodopsin (30,36,(45)(46)(47). In developing the protocol, we have specifically investigated the consequences of long time constant volume simulations for membrane-GPCR systems, after the volume has been equilibrated to 1 atm of pressure.…”
Section: Methodsmentioning
confidence: 99%